2012
DOI: 10.4314/ijbcs.v5i4.35
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à la dépollution des eaux usées de textile par électrocoagulation et par adsorption sur des composés à base de fer et d’aluminium

Abstract: RESUMELes ressources hydriques au monde sont rares et la demande en eau connaît une croissance continue en liaison avec l'évolution démographique et les activités consommatrices en eau, notamment les industries de textiles se voient dans l'obligation de recycler les eaux résiduaires et en particulier celles colorées. Dans ce travail, nous nous sommes intéressés à l'étude de l'élimination des matières organiques et colorantes de deux rejets provenant des industries de textile, un de teinture du tissu de polyest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Les colorants organiques sont des polluants persistants. Leur élimination appelle des méthodes appropriées (Zidane et al, 2011). L'élimination des colorants organiques ainsi que celles d'autres polluants organiques ou inorganiques des eaux usées s'avère donc nécessaire.…”
Section: Introductionunclassified
“…Les colorants organiques sont des polluants persistants. Leur élimination appelle des méthodes appropriées (Zidane et al, 2011). L'élimination des colorants organiques ainsi que celles d'autres polluants organiques ou inorganiques des eaux usées s'avère donc nécessaire.…”
Section: Introductionunclassified
“…These results are similar to those decrypted by some authors [33,34], in cooking breaking rice (WR) found to be not aggressive operation for sample containing more silicon. Studies showed that concentrated tomatoes caused more effect on cooking utensils [35]. Acidity of this product is so probability equivalent to those of fresh tomatoes, that is surely again a consequence of their origin and mode of production.…”
Section: Influence Of Media Ws and Wrmentioning
confidence: 92%
“…But these aluminium quantities released in the media are lower than media OR and OS. Studies showed that concentrated tomatoes caused more effect on cooking utensils (Karbouj, 2007;Zidane et al, 2011). Acidity of this product is so probability equivalent to those of fresh tomatoes, that is surely again a consequence of their origin and mode of production (Sawadogo et al, 2016).…”
Section: Influence Of Media O Os Tc and Ormentioning
confidence: 96%